Paradoxical gastrointestinal effects of interleukin-17 blockers. Issue 9 (21st July 2020) - Fauny, Marine; Moulin, David; D'Amico, Ferdinando; Netter, Patrick; Petitpain, Nadine; Arnone, Djesia; Jouzeau, Jean-Yves; Loeuille, Damien; Peyrin-Biroulet, Laurent
Abstract : Secukinumab, ixekizumab and brodalumab are monoclonal antibody therapies that inhibit interleukin (IL)-17 activity and are widely used for the treatment of psoriasis, psoriatic arthritis and ankylosing spondylitis. The promising efficacy results in dermatology and rheumatology prompted the evaluation of these drugs in Crohn's disease and ulcerative colitis, but the onset of paradoxical events (disease exacerbation after treatment with a theoretically curative drug) prevented their approval in patients with inflammatory bowel diseases (IBDs). To date, the pathophysiological mechanisms underlying these paradoxical effects are not well defined, and there are no clear guidelines for the management of patients with disease flare or new IBD onset after anti-IL-17 drug therapy. In this review, we summarise the literature on putative mechanisms, the clinical digestive effects after therapy with IL-17 inhibitors and provide guidance for the management of these paradoxical effects in clinical practice.